Favouritism Behaviours of School Administrators: Teachers’ Perceptions of the Secondary Schools in Turkey - Abidin Dağlı; Zühal Akyol (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
This study aims to determine favouritism behaviors of school administrators according to public secondary school teachers’ perceptions in terms of some variables. The sample of the study consisted of 22 schools selected randomly from the population and 376 teachers employed in these schools. “Favoritism in the School Management Scale